(untitled) (Texas Journal of Agriculture and Biological Sciences, 2022)
On the fields of winter wheat, the herbicide Atlantis was applied at various doses and terms, and its effectiveness against weeds was determined. Atlantis was applied at 250, 275, and 300 g/ha norms and observed after 30 days, weeds were destroyed 88.0-92.4% of monocotyledonous weeds and 87.8-91.6% of dicotyledonous weeds, with total weeds 87.8-91%. According to the norms of herbicides, it was found that the effectiveness against weeds was high up to 8.0-12.2%.